The Use of Institutional Repositories: Its Acceptance, Maturity, and Impact on the Book. - Swanepoel, Marinus (International Journal of the Book, 2013)
The development of institutional repositories (IR's) has been a recent one. IR's were started by the University of Southampton (UK) in late 2000 when the University released a software package called E-Prints. Since that time, the establishment of institutional repositories has gained momentum. Factors such as the decreasing costs of online storage and the increase of broadband and gigabit networking technologies have contributed to IR's growth in numbers and current popularity. The research is aimed answering several questions: 1) To what extent are IR's as a method for communicating scientific and scholarly information, accepted? This question is examined through the lens of the Gartner Hype Curve. 2) How mature is the institutional repository as a technology when using the product lifecycle (Sigmoid Curve) and diffusion of innovation theory as measures? 3) What is the evidence (if any) that institutional repositories are impacting the role of the book?